Active magnetic bearings used as exciters for rolling element bearing outer race defect diagnosis. (March 2016) - Xu, Yuanping; Di, Long; Zhou, Jin; Jin, Chaowu; Guo, Qintao
Abstract: The active health monitoring of rotordynamic systems in the presence of bearing outer race defect is considered in this paper. The shaft is assumed to be supported by conventional mechanical bearings and an active magnetic bearing (AMB) is used in the mid of the shaft location as an exciter to apply electromagnetic force to the system. We investigate a nonlinear bearing-pedestal system model with the outer race defect under the electromagnetic force. The nonlinear differential equations are integrated using the fourth-order Runge–Kutta algorithm. The simulation and experimental results show that the characteristic signal of outer race incipient defect is significantly amplified under the electromagnetic force through the AMBs, which is helpful to improve the diagnosis accuracy of rolling element bearing׳s incipient outer race defect. Highlights: Active magnetic bearings used as exciters for rolling element bearing defect diagnosis. The model of rolling element bearing with outer racer defect is created. There is significant increase in the vibration amplitude and peaks at f BPFO under electromagnetic force.